Diagnostic approach to restricted-diffusion patterns on MR imaging - Finelli, Pasquale F. (Neurol Clin Pract, 2012)
The vast majority of restricted-diffusion abnormalities result from acute stroke, and as such, the diagnosis may be problematic when this MRI feature results from other causes. Distinct patterns of restricted diffusion seen with various disease conditions can play an important diagnostic role. The association of certain diseases with a given restricted-diffusion pattern allows for a focused assessment to determine a specific etiology.